A Bootstrap-based Method to Achieve Optimality in Estimating the Extreme-value Index - Laurens F.M. de Haan; Liang Peng; T.T. Pereira (Tinbergen Institute, 1997)
Estimators of the extreme-value index are based on a set of upper order statistics. We present an adaptivemethod to choose the number of order statistics involved in an optimal way, balancing variance and biascomponents. Recently this has been achieved for the similar but somewhat less involved case of regularlyvarying tails (Drees and Kaufmann (1997); Danielsson et al.(1997)). The present paper follows the line ofproof of the last paper.
Keywords: 330; Schätztheorie; Theorie